STRATEGI BISNIS STARTUP MELALUI BUSINESS MODEL CANVAS: STUDI KASUS GOJEK DAN AIRBNB - K.M. Faisal Reza; KA. Noviansyah (Bajang Institute, 2024)
This study explores the application of the Business Model Canvas (BMC) in formulating business strategies that enable innovation and sustainability, focusing on the successful startups Gojek and Airbnb as case studies. BMC, a strategic management tool, provides a structured approach for startups to dissect and optimize their business models. This research delves into how Gojek and Airbnb utilized BMC to identify unique value propositions, adapt to market dynamics, and sustain long-term growth. Through a qualitative analysis, the study highlights the significance of BMC in fostering continuous innovation, strategic adaptation, and scalability in the competitive startup ecosystem. The findings underscore the importance of a holistic approach in business model formulation, continuous iteration based on market feedback, and the strategic alignment of business components to achieve sustainability and competitiveness. This research contributes to the understanding of BMC's practical application in startup strategy development, offering insights and recommendations for startups aiming to navigate the complexities of the modern market landscape